2011
DOI: 10.3109/11038128.2011.620984
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of perceived occupational gaps between people with stress-related ill health or musculoskeletal pain and a reference group

Abstract: Being on sick leave appears to start a process towards occupational deprivation where the areas that remain in the occupational repertoire become more important. Our study highlights the need to emphasize the whole occupational repertoire in rehabilitation and to facilitate engagement in valued activities to create a sound base for the process of returning to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…It is common for individuals suffering from stress-related mental illness to change their habits and daily routines, often isolating themselves in their own world of refuge. These people are at great risk of disengaging from everyday occupations, resulting in occupational disruption (7). The burden of not being able to meet the demands of the surrounding world or perform one's normal daily occupations gives rise to negative feelings such as lack of control over one's life, and life being meaningless (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It is common for individuals suffering from stress-related mental illness to change their habits and daily routines, often isolating themselves in their own world of refuge. These people are at great risk of disengaging from everyday occupations, resulting in occupational disruption (7). The burden of not being able to meet the demands of the surrounding world or perform one's normal daily occupations gives rise to negative feelings such as lack of control over one's life, and life being meaningless (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…These same results, however, are found in the general population. 32 The results relating to our last objective showed that among the partners with participation restrictions, the satisfied partners had lower anxiety and depression scores and fewer participation restrictions compared with dissatisfied partners. These analyses were explorative, and the results should be interpreted with caution because multiple comparisons were made.…”
Section: Discussionmentioning
confidence: 83%
“…For a group of patients with musculoskeletal pain or stress-related ill health, the mean number of gaps was 8.7. The Swedish reference group in the same study had 0-15 gaps, with a mean of 3.93 10 .…”
Section: Discussionmentioning
confidence: 94%
“…A survey of a Swedish reference group (n=711) 9 showed that the median number of occupational gaps was three for the whole sample, with some differences depending on age -younger persons had more gaps. In comparison, research has shown that the reference group reported fewer gaps than the rehabilitation groups of people with pain and stress-related disorders 10 and with stroke 11 .The existing information from the Swedish reference sample is continuously used for comparisons with different diagnostic groups to elucidate impact from illnesses/injuries on participation in everyday occupations.…”
Section: Introductionmentioning
confidence: 99%